Pemaknaan Hakikat Ilmu dalam Islam oleh Guru Pendidikan Agama Islam di Era Digital: Studi Fenomenologis - Abdullah, Bilal; Fadriati, Fadriati (Lembaga Yasin AlSys, 2025)
Although the nature of knowledge in Islam has been widely examined in Islamic education research, studies that specifically explore how Islamic Religious Education (PAI) teachers interpret the nature of knowledge in Islam in the digital era remain limited. This study aimed to explore how PAI teachers understand the nature of knowledge in Islam in the digital era, to identify digital factors that influence this understanding, and to explain its implications for teaching practices and teacher professionalism. The study employed a qualitative approach with a phenomenological design, involving ten PAI teachers selected through purposive sampling. Data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed using phenomenological thematic analysis techniques. The findings indicate that PAI teachers conceptualize knowledge in Islam as integrative, encompassing spiritual, rational, and empirical dimensions, and not only oriented toward cognitive aspects but also toward the formation of moral character. Digital factors, such as the use of online learning platforms and interactive digital media, influence how teachers understand and convey knowledge, although their use tends to be selective and adaptive to the epistemological values of Islam. These findings contribute to the development of contemporary Islamic educational epistemology and broaden understanding of the role of PAI teachers in responding to digital transformation. The study concludes that value-based digital literacy rooted in Islamic principles is crucial in teaching practice and encourages educational institutions and policymakers to develop programs that strengthen the professional competencies of PAI teachers in the digital era, while also opening avenues for further research on students’ perspectives and the effectiveness of digital-based PAI learning models.